Controls in vertical changes of alluvial system character. The «grésbelasianos» unit-Cretaceous of the Lusitanian Basin (Central Portugal) - Pena dos Reis, R.; Proenca Cunha, P.; Dinis, J.L. (Cuadernos de Geología Ibérica, 1994)
The ogrés belasianos» unit represents alluvial silicielastie sediments deposited during late Aptian to Cenomanian times in the Lusitanian Basin, on the western margin of the Iberian plate. Two fining-upward successions have been identitied in the unit by studies of vertical changes of lithofacies associations in tbe northern part of the basin. The Iower fining-upward succession corresponds to deposits of coalescent wet alluvial fans, changing to a braidplain witli local sinuosity. The upper succcss¡on records the transition from high slope braidplains with increasing sinuosity to fluvial-dominated deltaic deposits. Considering the available biostratigraphic data, the allocyclic controls on vertical changes of lithofacies assoeiations is discussed. It was inferred that the climate or a basin margin uplift were not the main control on system charaeter clianges. Furthermore, evidence in the offshore suggests that sea-level changes probably had a major influence. We believe that the onset of seafloor spreading in the Galician western margin and Bay of Biscay during upper Aptian to middle Albian have caused sea-level variations in the Lusitanian Basin, related to the thermal and isostatic adjustments. A relationship was admitted between the custatie curves of Haq et aL (1988) and the North Atíantie (Iberia included) geodynamic evolution. In the unit studied, the lower fining-upward succession probably corresponds to the supercycle LZB-4 and the upper tining-upward succession to UZA-í and part of the UZA-2 of Haq etal. (1988). Cuadernos de Geología Ibérica, nY 18, 27-5 8. Editorial Complutense, Madrid, 1994 L)ints, J. L. e, aL 28